TANTANGAN PESANTREN DALAM KOMERSIALISASI PENDIDIKAN DI TENGAH GLOBALISASI - Sholehuddin Sholehuddin (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2012)
This adult education including schools facing the challenge of globalization, which results insilaisasi komer education. In this era of human tradition to main-tain their existence through education included in its schools received a serious challenge, because education too real for some people used to accumulate tal ca-pitalization and profits. Education used as a commodity and not all people can access it. It is this fact that must be faced by the schools were able to provide the required service quality education at a low cost. Pesantren there was the ins-titution grow and develop in society and become a driving force of community itself, by him that, when the cost of education in schools is expensive or difficult to reach, then schools will alienate them from society.